Bypassing the Δ6‐desaturase enzyme and directly providing n‐3 and n‐6 PUFA pathway intermediates reduces the survival of two human breast cancer cell lines. Issue 9 (21st May 2015) - Yu, Howe‐Ming; Newell, Marnie; Subedi, Kalpana; Weselake, Randall J.; Mazurak, Vera; Field, Catherine J.
<x xml:space="preserve">Abstract</x> The n‐3 long chain polyunsaturated fatty acids (PUFA), eicosapentaenoic (EPA), and docosahexaenoic (DHA) acid, and in some studies, the n‐6 long chain PUFA arachidonic acid (AA), inhibit survival of breast cancer cells in vitro and in vivo. Less is known about the intermediates synthesized from the dietary 18 carbon fatty acids. The objective of this study was to determine the survival and phospholipid (PL) fatty acid composition of tumorigenic (MDA‐MB‐231, MCF‐7) and non‐tumorigenic (MCF‐12A) breast cells treated with intermediates in the n‐3 and n‐6 pathway. N‐3 intermediates, stearidonic acid (SDA) and eicosatetraenoic acid (ETA), and n‐6 intermediates, γ‐linolenic acid (GLA) and dihomo γ‐linolenic acid (DGLA), reduced (P < 0.05) the growth of tumorigenic but not MCF‐12A cells. All treatments resulted in a higher PUFA and saturated content and a lower monounsaturated content in tumorigenic cells (P < 0.05). For MDA‐MB‐231 PL, treatment with SDA and ETA increased ETA, EPA, and docosapentaenoic acid (DPA) and lowered AA, while treatment with GLA and DGLA primarily increased DGLA with only a small decrease in the DPA and DHA (P < 0.05). For MCF‐7 PL, due to low desaturase activity, the n‐3 intermediates increased ETA and the n‐6 increased DGLA (P < 0.05). Our findings suggest that the less studied n‐6 (GLA and DGLA) and n‐3 (SDA and ETA) fatty acids could serve as alternative dietary sources of bioactive lipids targeted at breast cancer. Practical applications: There is a growing body of literature suggesting that consumption of EPA and DHA can prevent and extend the life of the millions of women affected with breast cancer. This research explored the effect of treatment with fatty acid intermediates on the lipid composition and survival of human breast cancer cell lines. These intermediates bypass the rate limiting enzymes involved in desaturation of the dietary essential fatty acids. We provide evidence in vitro in two well‐established human breast cancer cell lines that providing intermediates in the n‐3 and n‐6 PUFA pathways reduce the survival of tumor cells. The resulting fatty acid composition of tumor phospholipids suggests that the mechanism of these fatty acids is unlikely due to increasing the content of the 20 and 22 carbon PUFA in the membrane. As few dietary sources of these intermediates exist, this study provides a rational to explore the development of novel animal and plant sources for their anti‐cancer activity. Further work is needed in animal models using patient derived xenographs to confirm that these changes occur in vivo. <inline-graphic xlink:href="ark:/27927/pgj2n17ws35" content-type="ejlt201400464-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Providing MDA‐MB‐231, MCF‐7, and MCF‐12A cells with n‐3 and n‐6 pathway intermediates after the Δ6 desaturase reduced growth of the two tumor cell lines and resulted in elongation of the intermediate fatty acids. Δ5 de‐saturation of fatty acids occurred in the n‐3 pathway.